Limitation of Freedom of Contract in Business Contract Drafting - Siti Syarifah Wafiqah Wardah; Muh. Rizal S.; Yusi Irensi Seppa; Andika Wahyudi Gani; Maya Kasmita (Universitas Negeri Makassar, 2023)
The principle of freedom of contract can be interpreted as the freedom of the parties to make or not make an agreement, the freedom to choose or determine with whom the business partner will carry out the agreement, then the freedom to choose the content and form of the things you want to make an agreement with. However, the freedom granted in the principle of freedom of contract is not absolute or without restrictions at all. The existence of this principle must be given restrictions so that contracts made by business people do not harm one of the parties involved in the agreement. This study aims to find out how to limit the principle of freedom of contract in designing business contracts and to find out the structure of designing business contracts. The type of research used in this study uses a normative juridical approach, in obtaining several sources of law in this study derived from primary, secondary and tertiary legal sources. The data collection technique used was a literature review technique (study document). The results of this study found that the principle of freedom of contract contains restrictions that may not be violated in order to create justice and equality of the parties